(untitled) (Nativa, 2024)
A aplicação foliar dos nutrientes N e Ni em estádio reprodutivo da soja pode trazer benefícios à cultura da soja. No entanto, ao se utilizar a ureia como fonte para essa prática é comum a ocorrência de fitotoxidez nas folhas. Essa fitotoxidez pode ser reduzida pela adição de Ni e sacarose à calda de pulverização. Assim, o presente trabalho teve por objetivo avaliar a aplicação de uma solução com diferentes concentrações de ureia, com e sem a presença de Ni e sacarose. O delineamento experimental utilizado foi em blocos casualizados, em esquema fatorial 4x2x2, com quatro repetições. Os tratamentos foram constituídos de quatro concentrações de ureia (0, 5, 10 e 15% m/v), na presença ou ausência de Ni (30 g ha-1 de Ni), com e sem adição de sacarose (1 mol L-1), aplicadas via folha no início da fase de enchimento de grãos. A aplicação foliar de ureia se mostrou viável somente com a adição de sacarose à calda de pulverização. A adição de sacarose na calda elimina a fitotoxidez nas plantas de soja causada pela aplicação de ureia. Não foram observados benefícios da aplicação isolada ou combinada de Ni e sacarose. Palavras-chave: Glycine max L.; nutrição de plantas; adubação nitrogenada; micronutriente; urease. Foliar fertilization of urea, nickel and sucrose in reproductive stage of soybean ABSTRACT: The foliar application of N and Ni nutrients in the reproductive stage of soybean can bring benefits to the soybean crop. However, when using urea as a source for this practice, the occurrence of phytotoxicity in the leaves is common. This phytotoxicity can be reduced by adding Ni and sucrose to the spray solution. Thus, the present work aimed to evaluate the application of a solution with different urea concentrations, with and without the presence of Ni and sucrose. The experimental design used was in randomized blocks, in a 4x2x2 factorial scheme, with four replications. The treatments consisted of four urea concentrations (0, 5, 10 and 15% w/v), in the presence or absence of Ni (30 g ha-1 of Ni), with and without the addition of sucrose (1 mol L- 1), applied to the leaves at the beginning of the grain filling phase. The foliar application of urea proved to be viable only with the addition of sucrose to the spray solution. The addition of sucrose in the spray solution eliminates phytotoxicity in soybean plants caused by urea. No benefits were observed from the isolated or combined application of Ni and sucrose. Keywords: Glycine max L.; plants nutrition; nitrogen fertilization; micronutrient; urease.